The complete mitochondrial genome of Lota lota (Gadiformes: Gadidae) from the Burqin River in China. (3rd May 2016) - Lu, Zhichuang; Zhang, Nan; Song, Na; Gao, Tianxiang
Abstract: In this study, the complete mitochondrial genome (mitogenome) sequence of Lota lota has been determined by long polymerase chain reaction and primer walking methods. The mitogenome is a circular molecule of 16, 519 bp in length and contains 37 mitochondrial genes including 13 protein-coding genes, 2 ribosomal RNA (rRNA), 22 transfer RNA (tRNA) and a control region as other bony fishes. Within the control region, we identified the termination-associated sequence domain (TAS), the central conserved sequence block domains (CSB-F and CSB-D), and the conserved sequence block domains (CSB-1, CSB-2 and CSB-3).